Of Hearts and Minds: Filipino Adult Viewers’ Message Interpretation Processing of Vaccination-Related Public Service Announcements - Flores, Jaime Manuel Q. (Plaridel Journal of Communication, Media, and Society; Vol 7 No 1 (2010): Health and Communication, 2011)
This study aims to fi nd out how Filipino adult viewers interpret vaccination-related public service announcements (PSAs), using the Message Interpretation Processing (MIP) framework by Austin, et al. (2001). Specifi cally, the study targets to: 1) determine the interpretation process used by viewers (logic-based or emotion-based); and 2) identify influential factors in relation to these interpretation processes. Data was acquired from 174 walk-in patients of three randomly selected barangay health centers in Parañaque City. Respondents answered a survey questionnaire after viewing three PSAs on rabies, polio and measles. Data were analyzed using correlation analysis and multivariate regression analysis. The study revealed that most viewers tend to interpret vaccination-related PSAs more logically than emotionally. Results also showed that logic-based interpretation is highly infl uenced by outcome expectancies, while emotion-based message interpretation processing is highly infl uenced by viewers’ close identification with PSA portrayals. Key words: health communication, message information processing, public service announcements, health promotion, health advocacy, message design